Food-to-Humans Bacterial Transmission - Antunes, Patrícia (2020)
Microorganisms vehiculated by food might benefit health, cause minimal change within the equilibrium of the host microbial community or be associated with foodborne diseases. In this chapter we will focus on human pathogenic bacteria for which food is conclusively demonstrated as their transmission mode to human. We will describe the impact of foodborne diseases in public health, the reservoirs of foodborne pathogens (the environment, human and animals), the main bacterial pathogens and food vehicles causing human diseases, and the drivers for the transmission of foodborne diseases related to the food-chain, host or bacteria features. The implication of food-chain (foodborne pathogens and commensals) in the transmission of resistance to antibiotics relevant to the treatment of human infections is also evidenced. The multiplicity and interplay of drivers related to intensification, diversification and globalization of food production, consumer health status, preferences, lifestyles or behaviors, and bacteria adaptation to different challenges (stress tolerance and antimicrobial resistance) from farm to human, make the prevention of bacteria-food-human transmission a modern and continuous challenge. A global One Health approach is mandatory to better understand and minimize the transmission pathways of human pathogens, including multidrug-resistant pathogens and commensals, through food-chain.